Distal airways are protected from goblet cell metaplasia by diminished expression of IL‐13 signalling components. Issue 9 (September 2015) - Vock, C.; Yildirim, A. Ö.; Wagner, C.; Schlick, S.; Lunding, L. P.; Lee, C. G.; Elias, J. A.; Fehrenbach, H.; Wegmann, M.
Summary Background Increased mucus production is a critical factor impairing lung function in patients suffering from bronchial asthma, the most common chronic inflammatory lung disease worldwide. Objective This study aimed at investigating whether goblet cell (GC) metaplasia and mucus production are differentially regulated in proximal and distal airways. Methods Female Balb/c mice were sensitized to ovalbumin (OVA) and challenged with an OVA‐aerosol on two consecutive days for 1 week (acute) or 12 weeks (chronic). Real‐time RT‐PCR analysis was applied on microdissected airways. Results In acutely and chronically OVA‐challenged mice, GC metaplasia and mucus production were observed in proximal but not in distal airways. In contrast, inflammation reflected by the infiltration of eosinophils and expression of the TH2‐type cytokines IL‐4 and IL‐13 was increased in both proximal and distal airways. Abundance of IL‐13Rα1 was lower in distal airways of healthy control mice. Under acute and chronic OVA‐exposure, activation of IL‐13Rα1‐dependent signalling cascade, reflected by Spdef and Foxo3A transcription factors, was attenuated in distal compared to proximal airways. Conclusion and Clinical Relevance These data indicate that distal airways might be less sensitive to IL‐13‐induced GC metaplasia and mucus production through lower expression of IL‐13Rα1 and attenuated activation of downstream signalling. This might represent a protective strategy to prevent mucus plugging of distal airways and thus impaired ventilation of attached alveoli.